Universal Pharmacare in Canada: A Prescription for Equity in Healthcare - Mohammad Hajizadeh; Sterling Edmonds (Kerman University of Medical Sciences, 2020)
Despite progressive universal drug coverage and pharmaceutical policies found in other countries, Canada remains the only developed nation with a publicly funded healthcare system that does not include universal coverage for prescription drugs. In the absence of a national pharmacare plan, a province may choose to cover a specific sub-population for certain drugs. Although different provinces have individually attempted to extend coverage to certain subpopulations within their jurisdictions, out-of-pocket expenses on drugs and pharmaceutical products (OPEDP) accounts for a large proportion of out-of-pocket health expenses (OPHE) that are catastrophic in nature. Pharmaceutical drug coverage is a major source of public scrutiny among politicians and policy-makers in Canada. In this editorial, we focus on social inequalities in the burden of OPEDP in Canada. Prescription drugs are inconsistently covered under patchworks of public insurance coverage, and this inconsistency represents a major source of inequity of healthcare financing. Residents of certain provinces, rural households and Canadians from poorer households are more likely to be affected by this inequity and suffer disproportionately higher proportions of catastrophic out-of-pocket expenses on drugs and pharmaceutical products (COPEDP). Universal pharmacare would reduce COPEDP and promote a more equitable healthcare system in Canada.